KONVERSI DAN KERUKUNAN UMAT BERAGAMA: Kajian Makna bagi Pelaku dan Elite Agama-agama di Malang - Sumbulah, Umi (Universitas Islam Negeri Raden Intan Lampung, 2013)
Islam gives freedom to people to choose their religions in accordance with their will and faith as stated in the Qur’an,2:256. For practitioners, the meaning of religious conversion is closely related to personal dimension that they feel; conversion as the shifting from something bad into the good one, the shifting from one religion into another, the shifting from inappropriate side into the appropriate side, and the appropriateness of long process of finding the God. For the religious elite, religious conversion is one dimension of religious freedom, which is closely related to the esoteric dimension experienced and perceived by the practitioners. Besides, pragmatic-practical motive in the form of marriage and promotion cannot be avoided in conversion case. In wider context, conversion can be understood as one of positive influence of inter-religious relationship in plurality context. However, it can be also a negative influence when the conversion is not based on strong belief in the new religion. Otherwise, the conversion is based on contemporary interest of the practitioners which is pragmatic and practical. The phenomenon of religious conversion mostly becomes destructive potential for the building of religious harmony, as in the religious community have triumphalistic ideology.